PENGARUH RETURN ON ASSET RETURN ON EQUITY NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM - Mujino Mujino; Pristin Prima Sari; Indah Wahyu Widiyanti (JURNAL ILMIAH EDUNOMIKA, 2021)
Analysis techniques using purposive sampling techniques. The purposive sampling method is a sample selection method based on population characteristics that have been determined. The sample in this study amounted to 15 LQ45 companies listed on the Indonesia stock exchange in 2015-2019. The author uses secondary data sources namely financial report resume data in the form of balance sheet and income statement obtained from the websites of each company that were sampled in this study during the observation period, namely 2015-2019. While the data collection method used is the documentation technique. The documentation technique is data collection which is done by looking at the data of each company and then quoting or copying it. in this study the data analysis technique used is multiple linear regression analysis supported by the classic assumption test. The results of this study are that the Return On Asset (ROA) has a negative and not significant effect on stock prices, Return On Equity (ROE) has a positive and significant effect on stock prices, Net Profit Margin (NPM) has a negative and significant effect on stock prices, Erning Per Share (EPS) has a positive and not significant effect on stock prices, and together Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Erning Per Share (EPS) have a significant effect on stock prices. Keywords : Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) Erning Per Share (EPS), Stock Prices.